PRESCHOOL EDUCATIONAL ORGANIZATION AS A MUSICAL AND EDUCATIONAL PHENOMENON - Shukurova Nilufar Gayratovna (Bright Mind Publishing, 2025)
The article provides information about the activities of currently opening musical kindergartens, how they differ from traditional kindergartens, and what methods are used in them.
Keywords: Musical kindergartens, musical perception, method, autonomous tradition, integrated tradition, development of talent in a child, playing a musical instrument.